The Level of Satisfaction of the Customer of Mr. D.I.Y at Ever Gotesco Mall: A Basis for Improving Customer Intervention Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, Filipinos, especially millennials and younger generations, are interested indifferent kinds of products that offer lower prices and good quality. Mr. D.I.Y is a retail chainthat offers a comfortable and enjoyable family shopping experience. It has an average floorspace of 10,000 square feet and offers ten categories of products with an average of 18,000varieties in each store. Mr. D.I.Y focuses on improving customer retention by providingexcellent service and satisfaction. However, some problems, such as inventorymanagement, product placement, and lack of employee knowledge, have been identified,which could negatively impact customer satisfaction. Therefore, Mr. D.I.Y must synchronizeinventory levels, maintain store cleanliness, train staff, and provide consistent quality andservice to retain customers.The respondents were 18-24 years old, both male and female, employed. 2.1 Thedescription of male and female groups of respondents assesses the customer level ofsatisfaction. “Very Strongly Agree” in terms of the Unique way of serving customers and theway welcoming the customer appreciated was presented to the customers. “Strongly Agree”Fast process of servicing and good communication of the employee to the customers. 3. Thedifference between the assessment of the 2 SOPs serving multiple customers “1st rank” 4.The hindrances experienced by the customers and the solution offered by the owner thehighest rank from males in “Serving multiple customers” and “shortage of the product” 5. Thecustomer retention program suggests offering incentives like discounts and exclusive accessto events, personalized communication, customer surveys, branded gifts, and exclusiveexperiences.Moreover, MR.DIY recognizes the importance of sustainability and corporate socialresponsibility, implementing various initiatives to reduce waste, conserve energy, andsupport local communities. In conclusion, MR.DIY has emerged as a dominant player in theretail industry, providing affordable, diverse, and high-quality products to millions ofcustomers. Its customer-centric approach, wide range of products, affordable pricingstrategy, and technological innovation have positioned it for future growth, making it a brandto watch in Southeast Asia.
Keywords: Business Administration